2021
DOI: 10.1038/s43856-021-00016-0
|View full text |Cite
|
Sign up to set email alerts
|

The teachings of Long COVID

Abstract: Long COVID is prolonged illness resulting from SARS-CoV-2 infection. Its serious implications for individuals and society have been missing from public communication and pandemic policy. Here, I draw on my lived experience, research, and advocacy work with Long COVID and reflect on the lessons learnt.Long COVID is the state of not recovering several weeks following acute infection with SARS-CoV-2, whether tested or not 1 . It is a patient-made 2 umbrella term for this condition, which may involve multiple path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…It was important for us to ask the questions that reflect the main areas of concerns expressed by pwLC. NAA experienced Long Covid Symptoms and has been a strong advocate of the recognition and measurement of the condition [ 34 , 35 ]. MEO and CH, as well as experiencing Long Covid themselves, have a wide overview of the symptoms, disability, disease course and concerns as expressed in the support groups and other national forums given their extensive involvement in Long Covid advocacy.…”
Section: Discussionmentioning
confidence: 99%
“…It was important for us to ask the questions that reflect the main areas of concerns expressed by pwLC. NAA experienced Long Covid Symptoms and has been a strong advocate of the recognition and measurement of the condition [ 34 , 35 ]. MEO and CH, as well as experiencing Long Covid themselves, have a wide overview of the symptoms, disability, disease course and concerns as expressed in the support groups and other national forums given their extensive involvement in Long Covid advocacy.…”
Section: Discussionmentioning
confidence: 99%
“…She has also written on patient involvement in long covid research and the lessons learnt that could apply to other conditions. 32 33 She contributed to informing this analysis’s concept, design, and interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…Validated instruments to measure patient reported outcomes have recently been developed to measure the global impact of long covid, and several unvalidated screening tools, surveys, and questionnaires are also available 1920. However, individuals living with long covid have suggested that existing self-report measures fail to capture the breadth of experienced symptoms 102122. To address the need for a comprehensive measure of self-reported symptom burden specific to long covid, we used Rasch analysis to develop and validate, in accordance with US Food and Drug Administration guidance, a novel instrument measuring patient reported outcomes, the symptom burden questionnaire for long covid (SBQ-LC) 1523…”
Section: Introductionmentioning
confidence: 99%